2017
DOI: 10.2514/1.c034036
|View full text |Cite
|
Sign up to set email alerts
|

Inlet Trade Study for a Low-Boom Aircraft Demonstrator

Abstract: Overland sonic boom challenges supersonic aircraft viability.! Current State-of-the-Art: ! • Adjoint-based shape optimization to match low-boom signature! • Isolated inlet, engine core, nozzle design and subsequent integration! Drawbacks: ! • Low-boom optimization neglects propulsion effects, sacrifices inlet/airframe performance & TSFC to meet low-boom objective! • Research shows introducing propulsion effects into a pre-optimized airframe pressure signature can compromise low-boom performance ! Propagated Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…There has been some recent work developing coupled propulsion-aerodynamic models for supersonic applications. Heath et al [26] manually coupled a RANS analysis to a propulsion model by matching the flow areas and states between the two and using the propulsion model to predict the static pressure for the fan-face boundary condition. This work compared the installed performance and sonic boom for two discrete inlet designs, and the limited number of configurations made manual coupling a reasonable approach.…”
Section: Fully Coupled Modelmentioning
confidence: 99%
“…There has been some recent work developing coupled propulsion-aerodynamic models for supersonic applications. Heath et al [26] manually coupled a RANS analysis to a propulsion model by matching the flow areas and states between the two and using the propulsion model to predict the static pressure for the fan-face boundary condition. This work compared the installed performance and sonic boom for two discrete inlet designs, and the limited number of configurations made manual coupling a reasonable approach.…”
Section: Fully Coupled Modelmentioning
confidence: 99%
“…1. The low-boom airframe was reverse-engineered from [4], with the axisymmetric spike inlet and propulsion flow path down-selected from the trade study in [7]. Modifications to the inlet were made for this study to improve off-design operation and are reported in Section III-A.…”
Section: Problem Definition a Baseline Vehicle Configuration Descriptionmentioning
confidence: 99%
“…The engine core paired with the inlet is representative of a General Electric F404-GE-402 afterburning turbofan, throttled to produce approximately 4500-lbf thrust at cruise with partial afterburner. As a result of engine installation in [7], vehicle sonic boom loudness was moderately compromised across the entire boom carpet. This study uses aerodynamic shape optimization to recover a portion of the sacrificed sonic boom loudness margin lost during engine integration.…”
Section: Problem Definition a Baseline Vehicle Configuration Descriptionmentioning
confidence: 99%
See 2 more Smart Citations